2014
DOI: 10.1007/s12013-014-9950-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alpha-2-Macroglobulin 5 bp I/D and Ile1000Val Polymorphisms on the Susceptibility of Alzheimer’s disease: A Systematic Review and Meta-analysis of 52 Studies

Abstract: Accumulating studies have evaluated the association of Alpha-2-Macroglobulin gene (A2M) 5 bp insertion/deletion (5 bp I/D, rs3832852) and Ile1000Val (rs669) polymorphisms with Alzheimer's disease (AD) risk, but the results remain inconclusive. To investigate whether these two polymorphisms facilitate the susceptibility to AD, we conducted a comprehensive systematic review and meta-analysis. Databases of PubMed, Embase, Web of Science, Medline, CNKI, and Google Scholar were searched to get the genetic associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that α2M −/− mice are resistant to the lethal effects of lipopolysaccharides 16 . α2M is also implicated in Alzheimer disease (AD) due to its ability to mediate the clearance and degradation of α-beta, the major component of beta-amyloid deposits 17 . However, role of α2M is yet to be determined in WNV infection and other inflammatory infectious diseases.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that α2M −/− mice are resistant to the lethal effects of lipopolysaccharides 16 . α2M is also implicated in Alzheimer disease (AD) due to its ability to mediate the clearance and degradation of α-beta, the major component of beta-amyloid deposits 17 . However, role of α2M is yet to be determined in WNV infection and other inflammatory infectious diseases.…”
Section: Resultsmentioning
confidence: 99%
“…1821 Moreover, early candidate gene analyses suggested that polymorphic variation in the A2M gene are associated with increased risk of AD, although these were not replicated in larger studies. 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Due to its protease inhibitory function, it can enhance procoagulant properties and possesses radioprotective effects. [23] In the eye, α 2 M is produced by retinal glia [11,12] and was found elevated as a soluble factor in the aqueous humor of eyes with glaucoma. [13] As true for other key proteins, α 2 M function is multifactorial, and includes, inhibiting the neuroprotective activity of nerve growth factor (NGF) through TrkA receptors, and enhanced the neurotoxic effect of proNGF through p75NTR receptor, α 2 M-LRP1 interactions, and immune bystander effects as well as glutamatergic stress.…”
Section: Discussionmentioning
confidence: 99%